Intrinsic factors driving mosquito vector competence and viral evolution: a review - Lewis, Juliette; Gallichotte, Emily N.; Randall, Jenna; Glass, Arielle; Foy, Brian D.; Ebel, Gregory D.; Kading, Rebekah C. (Frontiers in Cellular and Infection Microbiology, 2023)
Mosquitoes are responsible for the transmission of numerous viruses of global health significance. The term “vector competence” describes the intrinsic ability of an arthropod vector to transmit an infectious agent. Prior to transmission, the mosquito itself presents a complex and hostile environment through which a virus must transit to ensure propagation and transmission to the next host. Viruses imbibed in an infectious blood meal must pass in and out of the mosquito midgut, traffic through the body cavity or hemocoel, invade the salivary glands, and be expelled with the saliva when the vector takes a subsequent blood meal. Viruses encounter physical, cellular, microbial, and immunological barriers, which are influenced by the genetic background of the mosquito vector as well as environmental conditions. Collectively, these factors place significant selective pressure on the virus that impact its evolution and transmission. Here, we provide an overview of the current state of the field in understanding the mosquito-specific factors that underpin vector competence and how each of these mechanisms may influence virus evolution.